The Adult Literacy Classroom as a Social System - Hal Beder; Patsy Medina; Marian Eberly (Adult Education Research Conference, 2000)
This presentation reports the results of a study of adult literacy education classroom behavior in which twenty adult literacy classes were observed twice in seven states. It was found that in adult literacy classes the predominant mode of instruction closely parallels the initiation, response, evaluation (IRE) mode that Mehan (1979) identified in his study of an elementary education classroom.